EVATOR BIO-FOAM: INOVASI KEMASAN BIODEGRADABLE BERBASIS WIRAUSAHA MAHASISWA - Lubis, Mirna Rahmah; Muchlis, Muchlis; Zhafran, Muhammad; Rahman, Faris Izzatur (Kumawula: Jurnal Pengabdian Kepada Masyarakat, 2025)
The development of environmentally friendly products is an innovative solution to minimizing the harmful effects of waste on the environment. This innovation development program aims to formulate innovative strategies for developing Evator Bio-Foam products, made from rice husks, specifically for students through an entrepreneurship-based approach. Evator Bio-Foam, a rice husk-based product, is specifically targeted at university students through an entrepreneurship-based approach. Evator Bio-Foam is a biodegradable packaging material made from a mixture of rice husks, soybean flour, and yeast, which is fermented and molded into a functional alternative to Styrofoam. The product is lightweight, water-resistant, food-safe, and decomposes naturally within a relatively short time. The strategy employed in this program integrates learning, creativity, and entrepreneurship to increase students’ awareness of environmental sustainability while providing them with essential business skills. The methods used include training, workshops, and business simulations focusing on production, marketing, and product management. The results show that this approach enhances students’ understanding of environmentally friendly innovation and encourages active involvement in developing sustainable businesses. This educational model not only supports environmental conservation efforts but also creates new opportunities in entrepreneurship that are relevant to market needs. Thus, it offers a viable alternative for cultivating a generation that is environmentally conscious and oriented toward business innovation.Pengembangan produk ramah lingkungan menjadi solusi inovatif untuk mengurangi dampak negatif limbah terhadap lingkungan. Program pengembangan inovasi ini bertujuan untuk merumuskan strategi pengembangan produk Evator Bio-Foam berbahan dasar sekam padi, khususnya untuk mahasiswa, melalui pendekatan berbasis wirausaha. Evator Bio-Foam merupakan kemasan biodegradable yang dibuat dari campuran sekam padi, tepung kedelai, dan ragi, yang difermentasi dan dicetak menjadi produk pengganti styrofoam. Produk ini bersifat ringan, tahan air, aman untuk makanan, serta mudah terurai secara alami dalam waktu relatif singkat. Strategi yang digunakan dalam program ini mengintegrasikan pembelajaran, kreativitas, dan kewirausahaan guna meningkatkan kesadaran lingkungan mahasiswa sekaligus membekali mereka dengan keterampilan bisnis. Metode yang digunakan meliputi pelatihan, workshop, dan simulasi bisnis yang berfokus pada proses produksi, pemasaran, dan pengelolaan produk. Hasil program menunjukkan bahwa pendekatan ini mampu meningkatkan pemahaman mahasiswa tentang inovasi ramah lingkungan serta mendorong keterlibatan aktif dalam pengembangan usaha berkelanjutan. Model edukasi ini tidak hanya mendukung pelestarian lingkungan, tetapi juga menciptakan peluang baru di bidang kewirausahaan yang relevan dengan kebutuhan pasar. Dengan demikian, model edukasi ini dapat menjadi alternatif solusi untuk membangun generasi muda yang sadar lingkungan dan berorientasi pada inovasi bisnis.